Quotatives Indicating Quotations in Pāli Commentarial Literature, I Iti/ti and Quotatives with Vuttaṃ. - Kieffer-Pülz, Petra (Journal of Indian Philosophy, 2015)
This article deals with quotatives-overt marks that indicate quotations-consisting in iti/ti or containing vuttaṃ which are used in Pāli commentarial literature to signal the occurrence of a quotation. We distinguish two types, namely, 'general quotatives' and 'individual quotatives'. The former are universally valid. They are widely acknowledged and used in various text corpora over several centuries. The latter are defined by an author solely for usage in his commentary. In the first part of our contribution we describe the implications connected with the usage of quotatives, and depict the specific problems which may arise when a text including 'individual quotatives' is tacitly borrowed. In the second part we present some of the most common 'general quotatives' formed with the words iti/ti and vuttaṃ ( ti vuttaṃ, tena or ten' eva vuttaṃ; vuttañ c'/h' or vuttam pi c'/h' etaṃ, and vuttañ ca/hi). We aim at pointing out in which text layers a quotative is applied, for which text layers it is used, when it was in and when out of fashion.